Assessing uninstalled hydrogen-fuelled retrofitted turbofan engine performance - Farabi, Jarief; Mourouzidis, Christos; Pilidis, Pericles (MDPI, 2025)
Hydrogen as fuel in civil aviation gas turbines is promising due to its no-carbon content and higher net specific energy. For an entry-level market and cost-saving strategy, it is advisable to consider reusing existing engine components whenever possible and retrofitting existing engines with hydrogen. Feasible strategies of retrofitting state-of-the-art Jet A-1 fuelled turbofan engines with hydrogen while applying minimum changes to hardware are considered in the present study. The findings demonstrate that hydrogen retrofitted engines can deliver advantages in terms of core temperature levels and efficiency. However, the engine operability assessment showed that retrofitting with minimum changes leads to a ~5% increase in the HP spool rotational speed for the same thrust at take-off, which poses an issue in terms of certification for the HP spool rotational speed overspeed margin.
Keywords: hydrogen gas turbine; retrofitted engine; specific energy consumption (SEC); engine cycle efficiency; top of climb (TOC); end of runway (EOR)